IMPROVING STUDENTS’ LISTENING COMPREHENSION THROUGH YOUTUBE AT SMK MITRA NUSANTARA JATIBENING BARU PONDOK GEDE – BEKASI IN ACADEMIC YEAR 2023/2024 - ARSYASI KUSUMANING HATI; YON A.E; YANTI RUSMIATI (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the effectiveness of using YouTube as a medium to enhance English listening comprehension among students at SMK Mitra Nusantara, Bekasi, during the 2023/2024 academic year. Conducted as Classroom Action Research (CAR), the research involved a cyclical process of planning, action, observation, and reflection, targeting 25 students from class XI TKR. The data collection methods included observation and listening comprehension tests, analyzed through both qualitative and quantitative approaches. The results indicated a significant improvement in students' listening comprehension, as evidenced by the increase in average test scores from 70.4 in the pre-test to 71.92 in Cycle 1, and 81.24 in Cycle 2. Additionally, the number of students meeting the minimum competency criteria rose from 11 in the pre-test to 16 in Cycle 1 and 22 in Cycle 2. Qualitative observations also revealed heightened student engagement and motivation when using YouTube in the classroom. This study recommends that integrating YouTube into listening instruction can serve as an effective strategy for enhancing listening skills at the vocational high school level.